Ethnic divisions, political institutions and the duration of declines - Richard Bluhm; Kaj Thomsson (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes the duration of large economic declines and provides a theory of delayed recovery. First, we develop a formal political economy model that illustrates a simple mechanism of how weak constraints on the political executive can lead to longer declines in ethnically heterogeneous countries. The model shows how uncertain post-recovery incomes and a `winner-take-all' threshold effect create a commitment problem rendering a cooperative equilibrium inaccessible. Holding out can benefit groups by reducing the threshold effects in subsequent periods, thus limiting the remaining uncertainty. Placing strong constraints on the executive solves this commitment problem by reducing the uncertainty from the threshold effects, which brings about cooperation earlier on. Second, we then test several empirical predictions from the model using standard data on linguistic heterogeneity and more detailed data on ethnic power configurations. We find that the partial correlations are consistent with the proposed theory. The effect of executive constraints on the length of declines is very large in heterogeneous countries, but practically disappears in ethnically homogeneous societies. The adverse effect of heterogeneity is driven by the number of groups; increasing political concentration works in the opposite direction.
Keywords: E60; O43; J15; 330